TangShenWeiNing formula alleviates diabetic kidney disease by inhibiting ferroptosis via AMPK pathway in renal tubular epithelial cells - Jiang, Ye; Chang, Jing; Guo, You; Liu, Zhe; Feng, Xiaomeng (Frontiers in Endocrinology, 2026)
BackgroundDiabetic kidney disease (DKD) is a common microvascular complication of diabetes mellitus. Ferroptosis in renal tubular epithelial cells is a new hotspot in elucidating underlying molecular mechanism and treatment of DKD. Studies have shown that tubular lesions occur early in DKD, and high glucose induces cellular oxidative stress and promotes ferroptosis in tubular epithelial cells. TangShenWeiNing (TSWN) formula shows a beneficial therapeutic effect for alleviating DKD, but its underlying molecular mechanism remains enigmatic. Previous studies have suggested that TSWN formula alleviates DKD by regulating adenylate-activated protein kinase (AMPK) pathway.MethodsThe 8-week-old db/m and db/db mice were given low, medium, and high doses of TSWN as well as valsartan by gavage for 12 weeks, respectively.ResultsCompared with non-diabetic mice, diabetic mice showed elevated urinary albumin, which was reduced by treatment with TSWN or valsartan. Intrarenal fibrosis and type I collagen expression were induced in diabetic mice compared to nondiabetic mice. TSWN or valsartan treatment attenuated these effects. Renal tubular injury was increased in diabetic mice, but TSWN or valsartan treatment ameliorated this damage. Diabetes led to elevated iron levels in the renal tubules of mice, which were attenuated after treatment with TSWN or valsartan. The levels of intrarenal p-AMPK/t-AMPK were reduced in db/db mice compared with db/m mice, and were increased by treatment with TSWN or valsartan in db/db mice. Diabetes aggravated reactive oxygen species (ROS) formation in the kidneys of db/db mice, and this increase was inhibited by TSWN or valsartan treatment. Renal gp47phox was markedly upregulated in diabetic mice, whereas TSWN or valsartan administration significantly attenuated this elevation. Compared with db/m mice, db/db mice showed elevated renal malondialdehyde (MDA) and reduced expression of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidases (GSH-Px), and treatment with TSWN or valsartan lowered MDA while simultaneously restoring SOD, CAT and GSH-Px levels. Diabetic mouse kidneys exhibited marked downregulation of glutathione peroxidase 4, however, this reduction was reversed by TSWN formula or valsartan treatment in db/db mice.ConclusionsTSWN formula alleviated DKD by inhibiting ferroptosis via AMPK pathway in renal tubular epithelial cells.